Plastic deformation via hierarchical nano-sized martensitic twinning in the metastable β Ti-24Nb-4Zr-8Sn alloy. (1st August 2020) - Yang, Y.; Castany, P.; Hao, Y.L.; Gloriant, T.
Abstract: A superelastic metastable β Ti-24Nb-4Zr-8Sn (wt.%) alloy is analyzed in the solution treated state after different applied strains in order to reveal evolution of microstructures and explore plastic deformation mechanisms. Deformation bands are observed by optical microscopy, EBSD and TEM. After 3% of strain, only few thin {332}<113>β twins are observed, while after 5% of strain, complex hierarchically β twinning structures composed of primary and secondary bands are observed by TEM. Indeed, very thin secondary {332}<113>β twins are observed (about 50 nm in average) and their massive occurrence leads to the loss of the initial {332}<113>β twinning relationship between matrix and primary bands which is transformed passively to an unusual type II <531>β twinning relationship. Similarly, the orientation relationship between matrix and secondary twins tends to another abnormal type I {541}β twinning relationship. As in situ synchrotron XRD experiments show that almost all the β phase is transformed into α" martensite under loading condition, a crystallographic reconstructing method is then used to determine the real α″ orientation before stress releasing. The relaxed {332}<113> β twins is found to correspond perfectly to the reversion of {130}<310> α″ martensitic twins occurring under loading condition. The unusual twinning relationships between matrix and primary/secondary twins are shown to correspond to type II <512>α" and no twinning relationships in α" martensite, respectively. Schmid factor analyses show that the activation of primary twins obeys the Schmid law. However, the activation of secondary twins disobeys the Schmid law due to the variant selection of α" martensite occurring during primary twinning. Graphical abstract: Image, graphical abstract